ستراتيجية التنمية الإدارية في الفكر الإداري الكلاسيكي والحديث - الإبراهيمي, الطاهر; بوزيد, سليمة (University of Eloued جامعة الوادي, 2010)
تعتبر التنمية الإدارية الأداة الهامة والضرورية لإصلاح وتطوير الأجهزة الإدارية من أجل الرفع من مستوى كفاءتها؛ فهي تمثل القاعدة العملية التي تقف عليها مشروعات إدارة التنمية وخططها وأهدافها. ونظرا لهذه الأهمية التي تكتسيها التنمية الإدارية سنحاول إبراز جوانبها الأساسية كما تعرض لها كل من الفكر الإداري (الكلاسيكي والحديث) برؤية نقدية تقف عند جوانب القوة والضعف في طروحاتها ذات الصلة. Abstract Management development is important and necessary tool to rehabilitate and develop the administrative machinery for the lifting of the level of efficiency; it represents a practical rule, which stands for management projects and development plans and objectives. In view of this the importance of management development we will try to highlight the fundamental aspects of development against each of the management culture (classical and modern) and thereby show the strengths and weaknesses associated with this thought through the vision of a monetary objective.
رؤية نقدية
مقال بمجلة البحوث والدراسات
Keywords: ستراتيجية التنمية الإدارية - فكر إداري